Identifikasi Umur Formasi Jampang Anggota Cikarang Berdasarkan Kumpulan Nannofosil Gampingan di Sungai Cikarang, Geopark Ciletuh Pelabuhanratu - Pratiwi, Santi Dwi; Chiyonobu, Shun; Rosana, Mega Fatimah (Bulletin of Scientific Contribution, 2022)
The Cikarang river, Ciletuh  Palabuhanratu Geopark is composed of sandstones and claystones in various grain sizes and thicknesses with carbonate claystone thicknesses varying from 10 to 20 cm, which is part of the Jampang Formation Cikarang Member. A total of 35 samples with 70 preparate slides of nannofossils from one station at Cikarang River  were prepared for microscopic observation and identification of nannofossil datum based on the nannofossil assemblages. The biostratigraphic framework consisting of 8 zonal and non-zonal events based on the occurrences of 40 species of calcareous nannofossil from 35 samples on the Jampang Formation Cikarang Member at Cikarang River. Biostratigraphic interval at Site Cikarang River was correlated for the NN1 (22.6 Ma) to NN 4 (17.973 Ma) in Early Miocene Zone. Eight nannofossil datum species covered the Early Miocene interval these are as follows: the first common occurrence of Sphenolithus heteromorphus (NN4); last common occurrence of Sphenolithus belemnos  (NN4/NN3); last occurrences of  Sphenolithus dissimilis (NN3); first occurrence of  Sphenolithus belemnos (NN3/NN2); first common occurrence Helicosphaera carteri (NN2); last common occurrence of Triquetrorhabdulus carinatus (NN2); the first occurrence of  Sphenolithus disbelemnos (NN2/NN1);  and the first occurrence of Sphenolithus dissimilis (NN1). The most unusual feature is the abundance of Sphenolithus, productivity of Discoaster is rare and Cyclicargolithus is a reticulofenestrid coccolith that dominates (more than 50% of the assemblage) from younger to oldest age boundary samples.